BCR-ABL V280G Mutation, Potential Role in Imatinib Resistance: First Case Report. (4th April 2017) - Azevedo, Ana P; Reichert, Alice; Afonso, Celina; Alberca, Maria D; Tavares, Purificação; Lima, Fernando
Introduction: The identification of BCR-ABL expression as the defining leukemogenic event in chronic myeloid leukemia (CML) and the introduction of BCR-ABL tyrosine kinase inhibitors in 2001 have revolutionized disease management, leading to a reduction in mortality rates and accordingly an increase in the estimated prevalence of CML. Case report: Based on medical records and clinical follow-up, the authors present the case of a Philadelphia chromosome–positive CML patient who developed resistance to imatinib. Quantitative reverse transcription-polymerase chain reaction testing revealed a V280G BCR-ABL mutation. Discussion and conclusions: This is the first report describing a new BCR-ABL kinase domain mutation—V280G—that might be associated with resistance to imatinib. Approximately 15% to 30% of patients treated with imatinib discontinue treatment due to resistance or intolerance. More than 90 BCR-ABL mutations were detected so far, conferring variable degrees of drug resistance, with consequent clinical, therapeutic, and prognostic impact.